Cetrimonium Bromide Promoted Efficient Multi-component Protocol for Synthesis of 1-Amidoalkyl-2-naphthols in Aqueous Medium - Nakhate, A.V.; Ingale, A.P.; Shinde, S.V. (Asian Journal of Chemistry, 2021)
An efficient and eco-friendly cetrimonium bromide promoted one-pot synthesis of 1-amidoalkyl-2-naphthols by the multicomponent condensation of aldehydes, β-naphthol and amides in water is reported. The wide range of substrate scope, excellent yield, short reaction rate, operational simplicity and environmentally friendly water as medium are the prominent feature of this protocol.